C9orf72-associated neurodegeneration in ALS-FTD: breaking new ground in ribosomal RNA and nucleolar dysfunction - Herrmann, Dustin; Parlato, Rosanna (Cell & tissue research, 2018)
Amyotrophic lateral sclerosis (ALS) and frontotemporal degeneration (FTD) are neurodegenerative diseases with distinct clinical appearance. However, both share as major genetic risk factor a C9orf72 locus intronic hexanucleotide expansion. The pathogenic pathways associated with the expansion-dependent neuronal toxicity are still poorly understood. Recent efforts to identify common threads of neuronal dysfunction have pointed towards deficits of ribosomal RNA (rRNA) biogenesis and loss of nucleolar integrity, a condition known as nucleolar stress that is an emerging shared feature among neurodegenerative diseases. Intriguingly, the C9orf72 mutation in ALS-FTD interferes with the function of the nucleolus by transcripts and dipeptide repeats (DPRs) produced by the hexanucleotide expansion. Experimental discrepancies have given rise to different hypotheses with regard to the connection of C9orf72 and nucleolar activity. In this review, we present and discuss emerging concepts concerning the impact of C9orf72 expansion on nucleolar biology. Moreover, we discuss the “nucleolar stress hypothesis,” according to which nucleolar malfunction accompanies, exacerbates, or potentially triggers a degenerative phenotype. Upcoming awareness of the involvement of nucleolar stress in C9orf72 ALS-FTD could shed light into its pathogenesis, enabling potential treatment options aimed at shielding an “Achilles’ heel” of neurons.